The influence of alcohol abuse on agitation, delirium and sedative requirements of patients admitted to a general intensive care unit. (August 2019) - Stewart, Donald; Kinsella, John; McPeake, Joanne; Quasim, Tara; Puxty, Alex
Purpose: Patients with alcohol-related disease constitute an increasing proportion of those admitted to intensive care unit. There is currently limited evidence regarding the impact of alcohol use on levels of agitation, delirium and sedative requirements in intensive care unit. This study aimed to determine whether intensive care unit-admitted alcohol-abuse patients have different sedative requirements, agitation and delirium levels compared to patients with no alcohol issues. Methods: This retrospective analysis of a prospectively acquired database (June 2012–May 2013) included 257 patients. Subjects were stratified into three risk categories: alcohol dependency (n = 69), at risk (n = 60) and low risk (n = 128) according to Fast Alcohol Screening Test scores and World Health Organisation criteria for alcohol-related disease. Data on agitation and delirium were collected using validated retrospective chart-screening methods and sedation data were extracted and then log-transformed to fit the regression model. Results: Incidence of agitation (p = 0.034) and delirium (p = 0.041) was significantly higher amongst alcohol-dependent patients compared to low-risk patients as was likelihood of adverse events (p = 0.007). In contrast, at-risk patients were at no higher risk of these outcomes compared to the low-risk group. Alcohol-dependent patients experienced suboptimal sedation levels more frequently and received a wider range of sedatives (p = 0.019) but did not receive higher daily doses of any sedatives. Conclusions: Our analysis demonstrates that when admitted to intensive care unit, it is those who abuse alcohol most severely, alcohol-dependent patients, rather than at-risk drinkers who have a significantly increased risk of agitation, delirium and suboptimal sedation. These patients may require closer assessment and monitoring for these outcomes whilst admitted.